2016
DOI: 10.1186/s12967-016-1016-4
|View full text |Cite
|
Sign up to set email alerts
|

A validated cellular biobank for β-thalassemia

Abstract: Background: Cellular biobanking is a key resource for collaborative networks planning to use same cells in studies aimed at solving a variety of biological and biomedical issues. This approach is of great importance in studies on β-thalassemia, since the recruitment of patients and collection of specimens can represent a crucial and often limiting factor in the experimental planning. Methods:Erythroid precursor cells were obtained from 72 patients, mostly β-thalassemic, expanded and cryopreserved. Expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…For the study of β-thal, bio-banking is of special interest. A validated cellular biobank for β-thal cells has been recently reported [59]. The procedure includes cellular in vitro expansion, cryopreservation, storage in liquid nitrogen and, finally, thawing and sub-culturing.…”
Section: Bio-banking Of Erythroid Cellsmentioning
confidence: 99%
“…For the study of β-thal, bio-banking is of special interest. A validated cellular biobank for β-thal cells has been recently reported [59]. The procedure includes cellular in vitro expansion, cryopreservation, storage in liquid nitrogen and, finally, thawing and sub-culturing.…”
Section: Bio-banking Of Erythroid Cellsmentioning
confidence: 99%
“…New animal models, in vitro systems with potential to more closely mimic in vivo conditions and tools for gathering in vivo data in mice models are necessary for the advancement of BT therapies. A Thal-Biobank has been established with goals to supply researchers with the samples of the same cells for studies aimed at solving the plethora of biological and biomedical issues involved in using patient cell cultures 47 . Erythroid pre-cursors collected from 72 BT patients, were expanded, cryopreserved, characterized with respects their individual Hb profile and tested for abilities to produce HbF by hydroxyurea.…”
Section: Novel Tools For Drug Development and Therapy Discovermentioning
confidence: 99%
“…This finding suggests that Gγ-XmnI and Aγ(+25 G->A) polymorphisms should be present in both alleles for maximal potentiation of HbF production, even if not “per se” sufficient and probably acting with other “HbF modifiers”, since all the Gγ-XmnI(+/+) and Aγ(+25 A/A) patients did not carry any detectable alteration of the α-globin gene asset. In any case, the cellular system here described might help to dissect genetic control of fetal-hemoglobin persistence and disease phenotypes, especially considering the possibility to access cellular biobanks from β-thalassemia patients stratified with respect to genotype, Gγ-XmnI and Aγ(+25) polymorphisms, enabling cryopreservation and usage of the cryopreserved and thawed cells for molecular biology studies [ 31 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Clinical observations have shown that increased levels of fetal hemoglobin (HbF) can ameliorate the severity of the disorders of β-hemoglobin, including β-thalassemia [ 7 ]. High HbF levels are associated with transcriptional effects on the γ-globin genes, which are associated with the biological activity of several transcription repressors, including MYB, BCL11A, Oct-1, KLF1 and others [ 16 19 , 31 33 ]. A recent paper has pointed out the attention on a new putative repressor of the γ-globin gene, LYAR (human homologue of mouse Ly-1 antibody reactive clone), recognizing the Aγ-globin gene sequence 5′-GGTTAT-3′.…”
Section: Discussionmentioning
confidence: 99%